MARKETING AND BRANDING IN THE CONTEXT OF MODERN BUSINESS STRATEGY: A LITERATURE REVIEW OF PROMOTION STRATEGY, MARKET SEGMENTATION, PRICING, DISTRIBUTION, AND BRAND IDENTITY FORMATION THROUGH PERSONAL, PRODUCT, CULTURAL, AND GEOGRAPHIC BRANDING — A LITERATURE REVIEW - Iman Hikmat Nugraha; Gatot Dwiyono; Suherman (Adisam Publisher, 2026)
This study discusses marketing and branding in the context of modern business strategy through a literature review approach. The analysis focuses on the elements of marketing strategy, namely promotion strategy, market segmentation, pricing, and distribution, as well as brand identity formation through personal branding, product branding, cultural branding, and geographic branding. This study shows that modern marketing no longer stands alone but must be integrated with consistent branding practices to create differentiation, build brand equity, and strengthen long-term relationships with consumers. Through a synthesis of the literature, this study develops a conceptual framework that links the 4P/7P marketing mix with various branding approaches, thereby providing a theoretical basis for the development of more effective and sustainable business strategies in the digital age.